Microbe-Derived Antioxidants Protect IPEC-1 Cells from H2O2-Induced Oxidative Stress, Inflammation and Tight Junction Protein Disruption via Activating the Nrf2 Pathway to Inhibit the ROS/NLRP3/IL-1β Signaling Pathway - Cheng Shen; Zhen Luo; Sheng Ma; Chengbing Yu; Ting Lai; Shangshang Tang; Hongcai Zhang; Jing Zhang; Weina Xu; Jianxiong Xu (MDPI AG, 2024)
Oxidative stress can induce inflammation and tight junction disruption in enterocytes. The initiation of inflammation is thought to commence with the activation of the ROS/NLRP3/IL-1β signaling pathway, marking a crucial starting point in the process. In our previous studies, we found that microbe-derived antioxidants (MAs) showed significant potential in enhancing both antioxidant capabilities and anti-inflammatory effects. The main aim of this research was to investigate the ability of MAs to protect cells from oxidative stress caused by H2O2, to reduce inflammatory responses, and to maintain the integrity of tight junction proteins by modulating the ROS/NLRP3/IL-1β signaling pathway. IPEC-1 cells (1 × 104 cells/well) were initially exposed to 100 mg/L of MAs for 12 h, after which they were subjected to 1 mM H2O2 treatment for 1 h. We utilized small interfering RNA (siRNA) to inhibit the expression of NLRP3 and Nrf2. Inflammatory factors such as IL-1β and antioxidant enzyme activity levels were detected by ELISA. Oxidative stress marker ROS was examined by fluorescence analysis. The NLRP3/IL-1β signaling pathway, Nrf2/HO-1 signaling pathway and tight junction proteins (ZO-1 and Occludin) were detected by RT-qPCR or Western blotting. In our research, it was observed that MA treatment effectively suppressed the notable increase in H2O2-induced inflammatory markers (TNF-α, IL-1β, and IL-18), decreased ROS accumulation, mitigated the expression of NLRP3, ASC, and caspase-1, and promoted the expression of ZO-1 and Occludin. After silencing the NLRP3 gene with siRNA, the protective influence of MAs was observed to be linked with the NLRP3 inflammasome. Additional investigations demonstrated that the treatment with MAs triggered the activation of Nrf2, facilitating its translocation into the nucleus. This process resulted in a notable upregulation of Nrf2, NQO1, and HO-1 expression, along with the initiation of the Nrf2-HO-1 signaling pathway. Consequently, there was an enhancement in the activities of antioxidant enzymes like SOD, GSH-Px, and CAT, which effectively mitigated the accumulation of ROS, thereby ameliorating the oxidative stress state. The antioxidant effectiveness of MAs was additionally heightened in the presence of SFN, an activator of Nrf2. The antioxidant and anti-inflammatory functions of MAs and their role in regulating intestinal epithelial tight junction protein disruption were significantly affected after siRNA knockdown of the Nrf2 gene. These findings suggest that MAs have the potential to reduce H2O2-triggered oxidative stress, inflammation, and disruption of intestinal epithelial tight junction proteins in IPEC-1 cells. This reduction is achieved by blocking the ROS/NLRP3/IL-1β signaling pathway through the activation of the Nrf2 pathway.